Hyperimmunisation des donneurs de sang pour la production des gamma-globulines anti-Rh (D) - Archer, G.T.; Cooke, B.R.; Mitchell, K.; Parry, P. (Revue française de transfusion, 1969)
Un schéma est décrit pour la production d'anticorps anti-D à haut titre dans deux groupes de sujets Rh-négatifs, l'un non-immunisé précédemment et l'autre immunisé par grossesses ou par transfusions sanguines. De petites injections multiples de sang Rh-positif furent effectuées à des intervalles de cinq semaines sur une période de douze mois. Au bout des douze mois, 60 p. cent du premier groupe étaient immunisés mais avec un titre égal à la moitié du titre moyen du second groupe ; mais il semble probable que le titre moyen dans les deux groupes atteindra finalement un plateau à 2.000 (50 g/ml approximativement). Le développement d'anticorps non anti-Rh a compliqué ce schéma d'hyperimmunisation. A scheme is described for the production of high-titre anti-Rh(D) antibodies in two groups of Rh-negative subjects, one group not previously immunised and the other previously immunised by pregnancy or blood transfusion. Multiple small intravenous injections of Rh-positive blood were given at 5-week intervals, for an over-all period of 12 months. At the end of 12 months, 60 p. cent of the first group had become immune. The mean antibody titre rose progressively in both groups during the course of injections. At the end of 12 months the mean titre of those in the first group who had become immune was less than half the mean of the second group, but there are indications that the mean titre in both groups will eventually reach a plateau at 2,000 (approximately 50 g/ml). The development of non Rh antibodies was a complication of this scheme of hyperimmunisation.